Promoting the use of rat traps over pesticides in Cape Town's peri-urban areas : an analysis of factors influencing rat trap adoption - Roomaney, Rifqah (Department of Public Health and Family Medicine, 2015)
Rodent infestations are a common problem in low socio-economic areas surrounding Cape Town. The presence of rodents can lead to the contamination of food, damage of infrastructure and the spread of rodent-borne diseases. To control rodent infestations, people in these areas resort to the use of illegal street pesticides which can also compromise their health.